(untitled) (New York, 2002)
The goals of this Handbook for Texas Students are as follows. to acquaint you with the philosophy of the book, introduce you to educators from Texas who helped write the book and plan your coursework for the coming year, provide an opportunity for you to practice the skills you'll need for success and to help you practice and prepare for the TAAS Exam.
Keywords: English language,English language; Study and teaching,Readers